Evaluation of the Sensory Stimulation Intensity of Representative Spicy Flavor Substances Using Whole-Body Plethysmography - LIU Fuqiang, GUO Lulu, MAO Jian, CHAI Guobi, ZHANG Qidong, ZHANG Wenjuan, LIU Xingyu, ZHANG Tianbing, XIE Jiqing, XIE Jianping (Shipin Kexue)
This study aimed to investigate the impact of spicy stimuli on the respiratory status of rats inhaling aerosols of spicy substances. The intensity of spicy stimuli was characterized by examining changes in multiple respiratory function indicators. Changes in various respiratory function indicators of rats inhaling different concentrations of two representative spicy substances, capsaicin and nicotine, were monitored in real time using an unrestrained whole-body plethysmograph system fitted with a nebulized drug delivery device. The results demonstrated that sensory stimulation of capsaicin and nicotine elicited similar respiratory patterns, which were manifested by an enhancement of respiratory rhythm at low concentrations and a suppression of respiration at high concentrations. Low-intensity spicy stimulation elevated respiratory rate, reduced relaxation time, and increased mid-expiratory flow rate, while high-intensity spicy stimulation had reverse effects. Additionally, heightened spicy stimulus intensity resulted in a sustained increase in the airway narrowing index. Concentration effect curves corroborated an evident correlation between spicy stimulation intensity and respiratory function indicators. The sensory stimulation intensity of various spicy substances could be objectively characterized by monitoring changes in the airway narrowing index. This study has established a novel method for objectively assessing the sensory stimulation intensity of spicy substances, providing a novel mean and reference for further exploring the brain region effects underlying the perception of spicy flavor in experimental animals.